Modelling building energy use at urban scale: A review on their account for the urban environment. (November 2021) - Wong, Cyrus Ho Hin; Cai, Meng; Ren, Chao; Huang, Ying; Liao, Cuiping; Yin, Shi
Abstract: While more and more cities are planning towards sustainable development and climate resilience, a thorough understanding of the spatiotemporal pattern of building energy demand can be valuable for evidence-based city design and climate change mitigation. Energy demand in buildings is heavily influenced by its surrounding built and climatic environment. This requires simulation that is sensitive to the heterogeneity of buildings and climatic complications in dense urban settings. This paper provides a comprehensive review that documents and cross-compares the major methods to simulate building energy use at urban scale. The reviewed literature were acquired by using the search strings "urban-scale, city-scale or large-scale", "building energy, energy use, electricity use, energy consumption or thermal load" and "simulation, forecast, modelling or mapping" in the Web of Science database from 2010 to 2021. The result highlighted major differences in strengths, limitations and field of application of different methods based on modelling inputs, outputs and approaches to incorporate urban environment to the modelling. It also identified that future development of urban-scale building energy use should explore more ways to incorporate the spatial variation in weather and morphological conditions, especially in dense urban settings that experience greater environmental challenges. Highlights: Characterised the major methods to simulate building energy use at urban scale based on modelling input and outputs. Discussed and cross-compared existing approaches to incorporate the urban environment in simulations. Future effort should be put on the spatial variations in weather conditions in compact urban areas.